2021
DOI: 10.1021/acsnano.1c01878
|View full text |Cite
|
Sign up to set email alerts
|

Preventing Memory Effects in Surface-Enhanced Raman Scattering Substrates by Polymer Coating and Laser-Activated Deprotection

Abstract: The development of continuous monitoring systems requires in situ sensors that are capable of screening multiple chemical species and providing real-time information. Such in situ measurements, in which the sample is analyzed at the point of interest, are hindered by underlying problems derived from the recording of successive measurements within complex environments. In this context, surface-enhanced Raman scattering (SERS) spectroscopy appears as a noninvasive technology with the ability of identifying low c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 51 publications
1
28
0
Order By: Relevance
“…However, the irreversible capturing processes through either antibody‐antigen interaction, streptavidin‐biotin binding, enzymatic reaction, or DNA hybridization, [ 45–46 ] imposed a considerable interfering effect on subsequent measurements owing to the so‐called SERS memory effect. [ 47 ] This could compromise SERS measurements over time due to the changing surface conditions of the substrate. The repeated incubations are also time‐consuming, hindering the deployment of biosensor devices for rapid analytes screening.…”
Section: Resultsmentioning
confidence: 99%
“…However, the irreversible capturing processes through either antibody‐antigen interaction, streptavidin‐biotin binding, enzymatic reaction, or DNA hybridization, [ 45–46 ] imposed a considerable interfering effect on subsequent measurements owing to the so‐called SERS memory effect. [ 47 ] This could compromise SERS measurements over time due to the changing surface conditions of the substrate. The repeated incubations are also time‐consuming, hindering the deployment of biosensor devices for rapid analytes screening.…”
Section: Resultsmentioning
confidence: 99%
“…The SERS spectra confirm that the vibrational fingerprint of molecules in solution (4-mercaptobenzoic acid in this case) is only registered after opening a measurement window by sufficient laser irradiation. Adapted with permission from ref ( 186 ). Copyright ACS 2021.…”
Section: Optimization Of Substrates For Biological Applicationsmentioning
confidence: 99%
“…Finally, it has been recently reported that the irreversible adsorption of (analyte) molecules onto plasmonic substrates may interfere in subsequent measurements, which is known as the SERS-memory effect and represents a source of uncertainty in real-time measurements. 186 To resolve this issue, micron-thick, thermolabile polymer layers were deposited on top of plasmonic substrates, providing a physical barrier against molecular diffusion and adsorption. Laser irradiation at high fluence induces plasmonic heating of the underlying nanoparticles, so the sheathing layer degrades under high local temperature and opens a measurement window at the selected measurement time and location.…”
Section: Optimization Of Substrates For Biological Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along this direction, recently, Plou et al demonstrated a novel method to prevent the memory effect in microfluidic SERS measurements. 259 A non-permeable polymer layer was coated on a plasmonic SERS substrate to control the adsorption of analyte molecules. This polymeric layer was degraded by the same laser to create a micrometer sized window for consecutive SERS measurements.…”
Section: Sers Active Nanostructures For Microfluidic Sers and Their A...mentioning
confidence: 99%